The international responsibility of international organisations : cooperation in peacekeeping operations - Moelle, Moritz P. (Cambridge : Cambridge University Press, 2017)
The International Responsibility of International Organisations addresses the joint responsibility of organisations for violations of international law committed during the deployment of peacekeeping operations. More specifically, it inquires if and under which circumstances - in terms of the notion of control - international organisations can be jointly responsible. The author analyses the practice of international organisations (the United Nations, NATO, the European Union, the African Union and the Economic Community of West African States) on an inter-institutional level, as well as in the field in the form of five case studies. The likelihood and distribution of responsibility between international organisations engaged in peacekeeping operations is affected by the different layers of applicable primary norms (Security Council mandates, internal law of the organisations, international humanitarian and human rights law). Although external pressure may contribute to enhancing the effectiveness of holding international organisations jointly responsible, any substantial measures and mechanisms can only be implemented with the participation of states and international organisations.
Cooperation in peacekeeping and peace enforcement activities under the United Nations Charter -- The (emerging) system of collective security consisting of the United Nations and regional organisations -- From the broader legal framework to international responsibility -- The case-studies -- The law applying in peacekeeping operations -- Conclusions and recommendations.
Title from publisher's bibliographic system (viewed on 20 Mar 2017).
Keywords: Peacekeeping forces